2017 International comparison program for asia and the pacific purchasing power parities and real expenditures summary report. - Asian Development Bank. ([Manila] Asian Development Bank, 2020)
The report provides a comprehensive account of the 2017 International Comparison Program (ICP) cycle for 22 economies in Asia and the Pacific. It provides in-depth analyses of estimates of purchasing power parities (PPPs), total and per capita real (PPP-converted) gross domestic product and its component expenditures, and price level indexes showing relative costs of living. The PPPs enable comparison in real terms across economies by removing the price level differences among them. This report also presents in detail the conceptual framework and methodological approaches used in implementing the ICP.
Keywords: Purchasing power parity; Gross domestic product; Expenditures, Public; Consumption (Economics).; Electronic books